Teacher Orientations through Satellite Communication: Some Experiences - Pal, Rajendra; Pallai, Pratima (JOURNAL OF INDIAN EDUCATION, 2010)
The teacher training through distance mode is now an established system in India, especially after launching of dedicated satellite for education “EduSat”. National and state level agencies have been organising various training programs for teachers through EduSat. It has solved the problems of non availability of large number of competent resource persons, quality dilution and transmission loss during training and inability to cover large number of teachers at different locations. This paper is an attempt to review the history of teleconferencing in India and its various attempts with in the country including shift from one way video to two way video-conferencing through EduSat. The paper also highlights the research studies related to teleconferencing with special reference to programs and researches with EduSat. This paper is also an effort to describe the major programs conducted by CIET through EduSat for orientation of teachers of KVs, NVs and other CBSE affiliated schools for newly developed text books based on NCF, 2005.